The Quality Effect : Does Financial Liberalization Improve the Allocation of Capital? - Abiad, Abdul (IMF Working Papers; Working Paper ;, 2004)
The study documents evidence of a "quality effect" of financial liberalization on allocative efficiency, which is measured by the dispersion in Tobin's Q across firms. Based on a simple model, the authors predict that financial liberalization, by equalizing access to credit, reduces the variation in expected marginal returns. They test this prediction using a new financial liberalization index and firm-level data for five emerging markets: India, Jordan, Korea, Malaysia, and Thailand. They find strong evidence that financial liberalization, rather than financial deepening, improves allocative efficiency.